Prognostic value of glycolysis markers in pancreatic cancer: A systematic review and meta-analysis - Wang, Chengcheng; Xu, Ruiyuan; Song, Jianlu; Chen, Yuan; Yin, Xinpeng; Ruze, Rexiati; Xu, Qiang (Frontiers in Oncology, 2022)
Introduction: Previous studies have investigated the prognostic significance of glycolysis markers in pancreatic cancer; however, conclusions from these studies are still controversial. Methods: PubMed, Embase, and Web of Science were systematically searched to investigate the prognostic role of glycolysis markers in pancreatic cancer up to May 2022. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) related to overall survival (OS), disease free survival (DFS), recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) were calculated using the STATA 12.0 software. Results: A total of 28 studies comprising 2010 patients were included in this meta-analysis. High expression of the five glycolysis markers was correlated with a poorer OS (HR = 1.72, 95% CI: 1.34-2.22), DFS (HR = 3.09, 95% CI: 1.91-5.01), RFS (HR = 1.73, 95% CI: 1.21-2.48) and DMFS (HR = 2.60, 95% CI: 1.09-6.20) in patients with pancreatic cancer. In subgroup analysis, it was shown that higher expression levels of the five glycolysis markers were related to a poorer OS in Asians (HR = 1.85, 95% CI: 1.46-2.35, P < 0.001) and Caucasians (HR = 1.97, 95% CI: 1.40-2.77, P < 0.001). Besides, analysis based on the expression levels of specific glycolysis markers demonstrated that higher expression levels of GLUT1 (HR = 2.11, 95% CI: 1.58-2.82, P < 0.001), MCT4 (HR = 2.26, 95% CI: 1.36-3.76, P = 0.002), and ENO1 (HR = 2.16, 95% CI: 1.28-3.66, P =0.004) were correlated with a poorer OS in patients with pancreatic cancer. Conclusions: High expression of the five glycolysis markers are associated with poorer OS, DFS, RFS and DMFS in patients with pancreatic cancer, indicating that the glycolysis markers could be potential prognostic predictors and therapeutic targets in pancreatic cancer.